Heavily Indebted Poor Countries Initiative-Delivery of Debt Relief by Non-Paris Club Official Bilateral Creditors. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The table provides information on HIPC (Heavily Indebted Poor Country) Initiative debt relief provided by each non-Paris Club official bilateral creditor to post-completion point HIPCs. It tracks the HIPC Initiative debt relief granted by these creditors so far. The table will be updated annually in the context of the "HIPC Initiative Status of Implementation Report." It will also be updated when creditors and debtors provide comprehensive information for updating the estimates of HIPC Initiative debt relief provided.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Exit Meeting; HIPC Debt Relief; HIPC Initiative Assistance; Paris Club Meeting; PP; Brazil